PEMBERDAYAAN “RUMAH TAHFIDZ” DALAM PEMBENTUKAN KARAKTER SANTRI (Studi Pemberdayaan Masyarakat di bidang Keagamaan di Kabupaten Tanah Datar ) - Irwandi Irwandi (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Abstract Article 31 of the 1945 Constitution indicates the importance of education and regulation in the country which contains basic education which is interpreted as character education with personality growth. The character education in question essentially includes matters relating to religion, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the homeland, respect for achievement, friendly/communicative, peace-loving, fond of reading. , care for the environment, care about social, responsibility. In accordance with the demands of the 1945 Constitution, the local government together with the community realize a form of character education with the establishment of the